Brand Experience and Brand Equity: A Review and Future Research Agenda. - Madeira, Clara (2024)
Literature review in the domain of brand experience and brand equity is scarce as it is still developing, and most studies have focused on these two concepts separately. The purpose of this study is to understand the relationship between brand equity and brand experience by conducting a systematic review of both concepts. The systematic review is based on the analysis of literature collected from the Web of Science, using a global bibliometric analysis; social network analysis, and a descriptive analysis of the top-cited articles. The study reveals scientific research on the relationship between brand experience and brand equity was initiated in 2007. Brand experience is consistently considered an antecedent of brand equity. However, the data analysed showed a lack of diversity regarding markets, industries, and types of consumers studied. The study also proposes a conceptual framework of the main antecedents and outcomes of brand experience and brand equity that might be used to test and validate the influence of brand experience on brand equity. This study is the first systematic review focusing on the relationship between brand experience and brand equity, making it an original contribution in the field. DOI: https://doi.org/10.54663/2182-9306.2024.v.12.n.22.98-142